2019
DOI: 10.1002/app.48515
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric injectable fillers for cosmetology: Current status, future trends, and regulatory perspectives

Abstract: Injectable fillers have become a vital part of cosmetology. A wide variety of injectable fillers are developed for either correction of facial wrinkles and folds or facial contouring. As the most popular filler products, polymeric injectable fillers represent a class of the most common implantable medical devices. This review is intended to not only present current filler products, but also share perspectives of future trends, development processes, and regulatory considerations for the next generation of fill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 72 publications
(77 reference statements)
0
13
0
Order By: Relevance
“…This is particularly important for the clinical translation of hydrogel‐based carriers, implants, and devices, where the selection of the hydrogel base material, hydrogelation mechanism, and trigger are all highly dependent on the envisaged application and route of administration. Many hydrogel products have reached the market, [ 279 ] as part of surgical sealants (e.g., COSEAL, EVICEL fibrin sealant, or ReSURE ocular sealant), [ 280 ] wound dressings (e.g., Granugel), [ 281 ] antibacterial coatings (e.g., DAC), [ 282 ] dermal fillers (e.g., Restylane), [ 283 ] and cartilage repair matrices (e.g., CaReS). [ 284 ] Meanwhile, ongoing and future clinical trials are testing injectable hydrogel formulations for the treatment of knee osteoarthritis [ 285,286 ] and cartilage defects, [ 287 ] antibiotic‐loaded hydrogel coatings for hip implants, [ 288 ] and tissue‐marking hydrogels for radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important for the clinical translation of hydrogel‐based carriers, implants, and devices, where the selection of the hydrogel base material, hydrogelation mechanism, and trigger are all highly dependent on the envisaged application and route of administration. Many hydrogel products have reached the market, [ 279 ] as part of surgical sealants (e.g., COSEAL, EVICEL fibrin sealant, or ReSURE ocular sealant), [ 280 ] wound dressings (e.g., Granugel), [ 281 ] antibacterial coatings (e.g., DAC), [ 282 ] dermal fillers (e.g., Restylane), [ 283 ] and cartilage repair matrices (e.g., CaReS). [ 284 ] Meanwhile, ongoing and future clinical trials are testing injectable hydrogel formulations for the treatment of knee osteoarthritis [ 285,286 ] and cartilage defects, [ 287 ] antibiotic‐loaded hydrogel coatings for hip implants, [ 288 ] and tissue‐marking hydrogels for radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Silicone was also banned by the FDA for use as a dermal filler due to similar ensuing complications. 5 Despite this, use of these materials may occur especially by unlicensed providers due to lack of familiarity or experience, minimal regulation, or decreased cost, which may result in increased risk of severe patient complications that may be further exacerbated by poor knowledge of anatomy and injection technique, lack of sterile environments, and lack of patient follow-up after injection. Seok et al reported 3 cases of delayed inflammatory reactions following filler injection of an unknown material by unlicensed practitioners, with patients presenting with localized erythema and edema that waxed and waned despite oral immunosuppressants and antihistamines.…”
Section: Discussionmentioning
confidence: 99%
“…Biomaterials have been applied in the medical cosmetology for many years, such as filler materials and cosmetics. Filler materials can be injected in facial tissue to achieve facial rejuvenation, which requires safe and easy-to-operate biomaterials [ 324 ]. A few polymer materials have been developed for facial injection, such as polyacrylamide, hyaluronic acid, PLA and PLGA.…”
Section: Applications Of Biomaterials In Tissue Regenerationmentioning
confidence: 99%